Le Canada, le bilinguisme et le commerce - Arcand, Alan; Le Conference Board du Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
Le français est l’une des principales langues mondiales. Selon l’Organisation internationale de la francophonie (OIF), au moins 220 millions de personnes le parlent dans le monde1. C’est la langue officielle de tous les organismes des Nations unies et d’un grand nombre d’organisations internationales. Le français a pris naissance en France et s’est répandu grâce à l’expansion de ce pays outre-mer. Actuellement, quelque 30 pays dans le monde, dont le Canada, comptent le français parmi leurs langues officielles.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Les Québécois auraient besoin d’un nouveau contrat linguistique : Le rapiéçage, comme pour le projet de loi 14, est désuet / Quebecers Need a New Linguistic Social Contract : Piecemeal Approaches Like Bill 14 Are Outdated - D'andrea, Giuliano; Smith, Richard (2013)